Clinical profile of patients with posterior scleritis: A report from Eastern India - Kumar, Amitabh (Indian J Ophthalmol, 2018)
PURPOSE: This study aimed to report the clinical profile of patients with posterior scleritis at a tertiary eye center in Eastern India. METHODS: This was a single-center retrospective case series of patients who were diagnosed as posterior scleritis between January 2010 and December 2014, with a follow-up period of at least 6 months. RESULTS: The study included 18 patients of posterior scleritis with a mean age of 41.2 ± 10.6 years (range: 26–63 years). With female preponderance (55.6%), majority of the posterior scleritis cases were unilateral (88.9%). Sixteen patients reported with diminution of vision, eleven patients (61.1%) had ocular pain on presentation, and five patients complained of headache. Concurrent anterior scleritis was found in three eyes (15%) with posterior scleritis. Choroidal folds and subretinal fluid at the posterior pole were the most common fundus findings and were seen in seven eyes (35%) each. No systemic association was detected in any patient even after extensive laboratory workup and multidisciplinary consultation. All patients received oral steroid, and 11 (61.1%) of them required intravenous pulse steroid therapy. Immunosuppressive was used in 6 (33.3%) patients, and oral azathioprine was the most common immunosuppressive used in the study. Recurrence was noted in eight eyes (40%). The mean best-corrected visual acuity improved to logarithm of the minimal angle of resolution (logMAR) 0.06 ± 0.051 at the final follow-up from 0.47 ± 0.45 logMAR at presentation (P = 0.00608). CONCLUSION: Posterior scleritis is relatively rare but can occur without systemic involvement. Aggressive immunomodulatory therapy is required to treat vision-threatening condition.